DISTINGUISHING SYNONYMS IN ENGLISH: NUANCES AND CONTEXTUAL USAGE - Ergasheva Sabohat; Badalova Shahnoza (TADQIQOTLAR, 2026)
Abstract:  Synonymy  is  one  of  the  most  complex  aspects  of  the  English language. While dictionaries may define two words as having the same meaning, they are  rarely  interchangeable  in  every  context.  This  article  explores  the  linguistic boundaries of synonyms, focusing on how emotional intensity, collocation, and register distinguish them. A special emphasis is placed on the adverb "badly" and its diverse collocational  patterns  to  illustrate  how  synonym  choice  affects  grammatical  and semantic accuracy.